Longitudinal pain and pain interference in long‐term survivors of childhood cancer: A report from the Childhood Cancer Survivor Study. Issue 12 (30th March 2020) - Karlson, Cynthia W.; Alberts, Nicole M.; Liu, Wei; Brinkman, Tara M.; Annett, Robert D.; Mulrooney, Daniel A.; Schulte, Fiona; Leisenring, Wendy M.; Gibson, Todd M.; Howell, Rebecca M.; Srivastava, Deokumar; Oeffinger, Kevin C.; et al.
Abstract : Background: The objective of this study was to characterize the prevalence and risk of pain, pain interference, and recurrent pain in adult survivors of childhood cancer in comparison with siblings. Methods: This study analyzed longitudinal data from survivors (n = 10, 012; 48.7% female; median age, 31 years [range, 17‐57 years]; median time since diagnosis, 23 years) and siblings (n = 3173) from the Childhood Cancer Survivor Study. Survivors were diagnosed between 1970 and 1986 at 1 of 26 participating sites. Associations between risk factors (demographics, cancer‐related factors, and psychological symptoms) and pain, pain interference, and recurrent pain (5 years apart) were assessed with multinomial logistic regression. Path analyses examined cross‐sectional associations between risk factors and pain outcomes. Results: Twenty‐nine percent of survivors reported moderate to severe pain, 20% reported moderate to extreme pain interference, and 9% reported moderate to severe recurrent pain. Female sex, a sarcoma/bone tumor diagnosis, and severe/life‐threatening chronic medical conditions were associated with recurrent pain. Depression and anxiety were associated with increased risk for all pain outcomes. Poor vitality mediated the effects of anxiety on high pain and pain interference (root mean square error of approximation, 0.002). Conclusions: A large proportion of adult survivors report moderate to severe pain and pain interference more than 20 years after their diagnosis. Increased screening and early intervention for pain interference and recurrent pain are warranted. Abstract : In this longitudinal cohort analysis, compared with siblings, a large proportion of adult survivors of childhood cancer continue to report significant pain and pain interference decades after diagnosis. Enhanced screening and early intervention are warranted.